Force and conductance spectroscopy of second‐layer tin‐phthalocyanine on Ag(111). Issue 11 (13th August 2013) - Hauptmann, Nadine; Berndt, Richard; Frauenheim, Thomas; Niehaus, Thomas; Repp, Jascha; Richter, Klaus; Weber, Heiko
Abstract The conductance, frequency shift, and energy dissipation are measured during the formation of a contact to a single tin‐phthalocyanine (SnPc) molecule. The molecule is located on top of a first SnPc layer on Ag(111). The data show that subtle changes of the adsorption geometry cause drastic differences of the conductance, force, and dissipation signals.<inline-graphic xlink:href="ark:/27927/pgg3v1brsh6" content-type="pssb201349210-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Site‐dependent averaged conductance shift versus piezo displacement.